Leptobotia micra, a new species of loach (Teleostei: Botiidae) from Guilin, southern China - Bohlen, Jörg; Šlechtová, Vendula (Zootaxa, 2017)
Leptobotia micra, new species, is described from the upper Li River (Pearl River basin) around Guilin in Guangxi province, southern China. The new species is evidently the smallest species of Leptobotia, with females of 45‒46 mm SL bearing oocytes. It can be distinguished from all other species of Leptobotia by a combination of the following characters: no dark bars or dorsal saddles on body, a row of white dots along dorsal midline, 4+34 vertebrae, a predorsal distance of 58.1‒59.0% SL, eye diameter 1.8‒2.0 % SL, pelvic fins not reaching anus, an emarginated caudal fin (length of median rays 1.3‒1.4 times in length of lower lobe) and the anus positioned distinctly closer to anal-fin origin than to pelvic-fin base.